Non-Standard Employment after Age 50: How Precarious Is It? - D'Amours, Martine (Relations industrielles / Industrial Relations, 2009)
Based on a qualitative study of the trajectories of 22 workers aged 50 or older who lost or left a standard job and then undertook some form of non-standard employment, this article wants to shed light on the quality of non-standard jobs often held by seniors. Can these jobs be categorized as precarious, and if so, what are the dimensions of this precariousness? Our analysis enabled us to identify three main profiles: early retirees, "competitive" non-standard workers, and vulnerable non-standard workers. This diversity is mainly related to the characteristics of the previous occupational trajectory but also to the characteristics of the repositioning job, the type of skills the worker has, gender, age, and the fact of living or not with a spouse.
Keywords: Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Employment; LABOR market; Labor Unions; Older workers; Quality of work; Retirement; Sampling techniques; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z; Studies

Les intermittents du spectacle. Sociologie d'une exception - D'Amours, Martine (Relations industrielles / Industrial Relations, 2008)
The article reviews the book, :Les intermittents du spectacle. Sociologie d’une exception," by Pierre-Michel Menger.
Keywords: Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Labor Unions; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z

Les dimensions de l’hétérogénéité de la catégorie de travailleur indépendant sans employé : Éléments pour une typologie - D’Amours, Martine; Crespo, Stéphane (Relations industrielles / Industrial Relations, 2004)
Le présent article vise à décrire et à expliquer la diversité des situations couvertes par la catégorie juridique de travailleur indépendant (travailleur autonome sans employé). Utilisant les méthodologies de l’analyse factorielle de correspondances multiples et de la classification ascendante hiérarchique, il analyse l’hétérogénéité au sein d’un échantillon de 293 travailleurs indépendants, autour de cinq dimensions : les caractéristiques du producteur, la nature de sa clientèle, le type de produit, l’organisation du travail (incluant la rémunération) et la protection contre les risques sociaux et professionnels. Ce faisant, il contribue à dégager six profils de travailleurs indépendants : les non-professionnels indépendants, les petits producteurs dépendants, les professionnels libéraux, les conseillers et consultants, les autres indépendants et ceux cumulant travail indépendant et salariat atypique et, finalement, les professionnels bénéficiant d’ententes collectives de travail. Il illustre par ailleurs qu’une partie de cette hétérogénéité est attribuable au brouillage des frontières entre les modèles « purs » de salariat et d’indépendance.